Eigenvalue Productivity: Measurement of Individual Contributions in Teams - Julia Müller; Thorsten Upmann (Center for Economic Studies and ifo Institute (CESifo), 2017)
While the output of a team is evident, the productivity of each team member is typically not readily identifiable. In this paper we consider the problem of measuring the productivity of team members. We propose a new concept of coworker productivity, which we refer to as eigenvalue productivity (EVP). We demonstrate the existence and uniqueness of our concept and show that it possesses several desirable properties. Also, we suggest a procedure for specifying the required productivity matrix of a team, and illustrate the operational practicability of EVP by means of three examples representing different types of the available data.
Keywords: D24; J24; L23; 330; coworker productivity; eigenvalue productivity; centrality; team production